2009
DOI: 10.1121/1.3203562
|View full text |Cite
|
Sign up to set email alerts
|

Sound pressure and particle acceleration audiograms in three marine fish species from the Adriatic Sea

Abstract: Fishes show great variability in hearing sensitivity, bandwidth, and the appropriate stimulus component for the inner ear (particle motion or pressure). Here, hearing sensitivities in three vocal marine species belonging to different families were described in terms of sound pressure and particle acceleration. In particular, hearing sensitivity to tone bursts of varying frequencies were measured in the red-mouthed goby Gobius cruentatus, the Mediterranean damselfish Chromis chromis, and the brown meagre Sciaen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 54 publications
5
74
0
Order By: Relevance
“…5). Previous studies have already measured behavioral audiograms in holocentrids (Tavolga and Wodinsky, 1963;Coombs and Popper, 1979), as well as AEP audiograms in a few pomacentrids (Egner and Mann, 2005;Wright et al, 2005;Wysocki et al, 2009) and chaetodontids (Webb et al, 2012;Tricas and Boyle, 2015). However, direct comparison of these studies with our AEP traces can be irrelevant because audiograms produce very different results depending on the methodology used (i.e.…”
Section: Interspecific Differences In Auditory Capabilitiesmentioning
confidence: 46%
“…5). Previous studies have already measured behavioral audiograms in holocentrids (Tavolga and Wodinsky, 1963;Coombs and Popper, 1979), as well as AEP audiograms in a few pomacentrids (Egner and Mann, 2005;Wright et al, 2005;Wysocki et al, 2009) and chaetodontids (Webb et al, 2012;Tricas and Boyle, 2015). However, direct comparison of these studies with our AEP traces can be irrelevant because audiograms produce very different results depending on the methodology used (i.e.…”
Section: Interspecific Differences In Auditory Capabilitiesmentioning
confidence: 46%
“…Consistent with previous studies, acceleration measurements were collected in three dimensions relative to fish orientation inside the tank: x (anterior/posterior), y (left/right) and z (dorsal/ventral) (Casper and Mann 2006;Horodysky et al 2008;Wysocki et al 2009) using a custom-modified three-dimensional underwater accelerometer (PCB model VW356A12, sensitivity = 100 mV g −1 (10.2 mV ms −2 ) PCB Piezotronics, Depew, NY) that was encased in syntactic foam and epoxy to make it neutrally buoyant. We characterized the acoustic impedance (ratio of sound pressure to particle velocity) of our experimental tank conditions as suggested by Popper and Fay (2011), using the calibration measurements at different three SPLs: 118, 130, and 145 dB (re.…”
Section: Acoustic Stimulus Generation and Calibrationmentioning
confidence: 95%
“…Because there was a linear relationship between pressure and particle motion at all frequencies tested, best-fit linear transformations were derived for each frequency using pressure calibration measurements and the equivalent particle motion measurements in the x, y and z axes. After deriving thresholds in the x, y and z dimensions, particle motion threshold reported as the combined magnitude vector, calculated as 20 log (√(x 2 + y 2 + z 2 )) similar to Wysocki et al (2009) …”
Section: Data Analysesmentioning
confidence: 99%
“…less straightforward than that in cichlids and holocentrids (Ramcharitar et al, 2004(Ramcharitar et al, , 2006Horodysky et al, 2008;Wysocki et al, 2009). Ramcharitar et al (2006) showed that the swim bladder in the weakfish Cynoscion regalis has anterior horns that terminate close to the ears and that this species detects sound frequencies up to 2 kHz.…”
Section: Sciaenidae (Drums and Croakers)mentioning
confidence: 99%